PERAN KEPEMIMPINAN, PENDIDIKAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI BAPENDA KABUPATEN SITUBONDO DAN BONDOWOSO DENGAN LOYALITAS KERJA SEBAGAIVARIABEL INTERVENNING - Karim, Kurniawan; Karnadi, Karnadi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze the influence of variablesEducational Leadership and Organizational Culture on Employee Performance in the Situbondo and Bondowoso Regency Bapenda with Work Loyalty as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Leadership has a significant positive effect on Employee work loyalty, Education has a significant positive effect on Employee work Loyalty, Organizational culture has a significant positive effect on Employee work Loyalty, Leadership has a positive but not significant effect on Employee performance, Education has a significant positive effect on Employee Performance, Organizational culture has a significant positive effect on EmployeePerformance, Employee work loyalty has a significant positive effect on Employee Performance, Leadership has a positive but not significant effect on Employee Performance through Employee work Loyalty, Education has a positive but not significant effect on Employee Performance through Employeework Loyalty , and Organizational culture has a positive but not significant effect on Employee Performance through Employee work Loyalty.